Strengthening Ergonomics and OHS Literacy through the Ergoschool Program in Vocational Education (TEKAD : Teknik Mengabdi, 2025)
The Ergoschool 2024 program was designed to enhance students’ literacy and awareness of ergonomics as well as occupational health and safety (OHS) in vocational education settings. Implemented at vocational school, the program adopted an interactive learning approach that included pre-tests, post-tests, structured lectures, simulations, and educational games. The training materials were organized into five main modules, integrating ergonomic principles with OHS practices. Evaluation results indicated a significant improvement in students’ knowledge, as reflected in the comparison between pre-test and post-test scores. Beyond improving theoretical understanding, the program also fostered preventive attitudes toward occupational risks and strengthened students’ readiness for the industrial workplace. Despite limitations in duration and coverage, the initiative demonstrates strong potential for replication and expansion to other vocational schools. Thus, Ergoschool can be considered a sustainable educational model for cultivating a safe, healthy, and ergonomic work culture in vocational education.